Studi Komparatif antara Ragam Hias Batik Tradisional Bakaran dengan Ragam Hias Batik Keraton Surakarta - Ulfa Septiana; Yan Yan Sunarya; Achmad Haldani (Journal of Visual Art and Design, 2013)
Bakaran batik is a batik that is developed in Bakaran Village, Pati Regency at the North Coast of Java. Traditional ornaments in Bakaran batik show no influence from foreign cultures in general coastal batik, but are similar to the ornamentation of the Keraton Surakarta batik. This study aims to describe the elements of ornamentation and aesthetic characteristics of traditional Bakaran and Keraton Surakarta batik, and to identify the cause of the similarity between them. The conclusion is the ornamentation of Bakaran traditional batik and Keraton Surakarta one, have similarities to the main motive of the batik ornaments, that occur between Bakaran traditional batik and Keraton Surakarta one were caused by the trade relations between regions of both batiks in the past. There are also differences that characterize these batiks, the size and shape of the batik motifs on the traditional batik.